Magnetna resonanca, pojav z velikim medicinskim potencialom, a zapletenim fizikalnim ozadjem - Božič, Bojan (Zdravniški vestnik, 2013)
Magnetic resonance imaging is a very complex diagnostic technique. Therefore, both practical experiences and theoretical understanding is needed for effective diagnostics. It is therefore important that physicians are sufficiently familiar with the basic physical principles of magnetic resonance. In the interpretation of physical concepts, we will rely both on the classical aswell as on the quantum-mechanical view of the signal formation in magnetic resonance, which are to some extent complementary. The signal appearance in magnetic resonance imaging willbe discussed. A special emphasis will be put on the role of the resonance frequency and the pulse sequences. Furthermore, the spin echo as one of the most used classical signal sequences in diagnostic investigations will be described.
Keywords: magnetic resonance; magnetna resonanca; pulse sequence; resonance frequency; resonančna frekvenca; sunkovno zaporedje